Penguatan Kapasitas Pendidik PAUD Mewujudkan PAUD Berkualitas Secara Holistik Integratif - Misnawati Misnawati (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Early Childhood Education (PAUD) is an important stage in children's development that has a long-term impact on their future. Therefore, the quality of education at an early age must be a top priority. One way to improve the quality of PAUD is through strengthening the capacity of educators. Competent and empowered educators can create a conducive learning environment and support children's holistic development. This article examines the importance of strengthening the capacity of PAUD educators in realizing quality education in a holistic and integrative manner. Strengthening the capacity of PAUD educators involves providing the training, resources and support necessary to increase the competency and professionalism of educators. Educators equipped with the right knowledge and skills can better implement an integrative holistic approach. This means that educators are able to integrate various aspects of children's development, including physical, cognitive, emotional, social and moral, in daily learning activities. Children also get a more comprehensive and balanced learning experience, which supports their optimal development.